2016
DOI: 10.1590/2175-353920150201930
|View full text |Cite
|
Sign up to set email alerts
|

Considerações Sobre a Habilidade de Compreensão em Leitura e Formas de sua Avaliação

Abstract: ResumoA compreensão leitora é uma atividade complexa que envolve mecanismos cognitivos, linguísticos, sociais e emocionais. Nas sociedades ocidentais, o êxito escolar muito se relaciona a uma apreensão adequada do processo de ler e compreender o texto lido, sendo um dos requisitos para a aprendizagem. Assim, a compreensão da leitura é assunto relevante àqueles que trabalham com a educação e com problemas dela decorrentes. Este trabalho se insere nesse contexto e objetiva fornecer uma exposição geral sobre o es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 30 publications
0
7
0
1
Order By: Relevance
“…Creating alternative or parallel forms of an instrument is referred as the best way we can compare test scores across different sets of items that supposedly measure the same construct (American Educational Research Association et al, 2014). In a review, Oliveira et al (2016) showed there are few standardized measures for evaluating reading comprehension among Brazilian children, and these lacked construct validation and reliable norms. The great majority of the instruments were not commercialized (they were available only in dissertations, chapter books, and papers) and none of the revised instruments presented item analysis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Creating alternative or parallel forms of an instrument is referred as the best way we can compare test scores across different sets of items that supposedly measure the same construct (American Educational Research Association et al, 2014). In a review, Oliveira et al (2016) showed there are few standardized measures for evaluating reading comprehension among Brazilian children, and these lacked construct validation and reliable norms. The great majority of the instruments were not commercialized (they were available only in dissertations, chapter books, and papers) and none of the revised instruments presented item analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Both Anele and PROCOMLE instruments are composed of multiple-choice questions (though the former additionally presents a free retelling). Finally, the instrument by Saraiva et al (2020) cited by Oliveira et al (2016) received a new edition in 2020. Albeit some improvements were observed in terms of construct description and scoring, it still does not present item analysis or validity and reliability reports.…”
Section: Introductionmentioning
confidence: 99%
“…It requires the use of several combined cognitive skills that demand interaction between the reader and the text Mota, 2015). It includes elements such as vocabulary knowledge, linguistic and semantics decoding, inferring, analysis, synthesis, creativity, and also relating the content with other knowledges previously acquired (Oliveira, Lúcio & Miguel, 2016a;Oliveira, Santos, Boruchovitch & Rueda, 2012a). According to Corso, Piccolo, Miná & Salles (2015), reading comprehension is not established only by internal causes such as the cognitive ability of each subject, but also depends on external causes such as the learning environment and reading practices involved in the process.…”
mentioning
confidence: 99%
“…In the school context, reading goes beyond the acquisition of knowledge, it allows the development of the students' critical thinking, enabling them to analyze and question the contents read from their own ideas and personal values . Oliveira et al, 2016a).…”
mentioning
confidence: 99%
See 1 more Smart Citation